PCR-DGGE-based study of fecal microbial stability during the long-term chitosan supplementation of humans - Mrázek, J; Koppová, I; Kopecný, J; Simůnek, J; Fliegerová, K (Folia microbiologica, 2010)
A feeding study was performed to monitor the effect of chitosan intake on the fecal microbiota of ten healthy human subjects. Diversity of microflora was monitored during 8 weeks including 4 weeks of chitosan supplementations. Using denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA gene amplicons and quantitative PCR method we revealed possible changes originating in the overall bacterial composition and also in the subpopulation of Bifidobacterium group. DGGE profiles displayed high complexity and individuality for each subject. Considerable variations in the composition of band patterns were observed among different persons. A raised level of fecal Bacteroides in response to chitosan intake was found in all samples. Bifidobacterium levels following chitosan intake increased or remain unchanged. Non-significant increase was, surprisingly, found in the numbers of butyrate-producing bacteria.
Keywords: Electrophoresis, Polyacrylamide Gel; denaturace nukleových kyselin; DNA bakterií; Chitosan; feces; Human Experimentation; Humans; elektroforéza v polyakrylamidovém gelu; experimenty na lidech; lidé středního věku; DNA, Ribosomal; Female; dospělí; RNA ribozomální 16S; lidé; Bacteroides; RNA, Ribosomal, 16S; Feces; Adult; DNA, Bacterial; ženské pohlaví; biodiverzita; Male; Middle Aged; Nucleic Acid Denaturation; polymerázová řetězová reakce; Polymerase Chain Reaction; ribozomální DNA; Bifidobacterium; mužské pohlaví; chitosan; Biodiversity